2013
DOI: 10.1002/pen.23797
|View full text |Cite
|
Sign up to set email alerts
|

A composite model for starve fed single screw extrusion of thermoplastics

Abstract: A composite model has been developed to simulate a starve fed single screw extrusion of thermoplastics. The model is based on combining melt conveying models with new melting models. Illustrative computations are made for low-density polyethylene and polypropylene at various operating conditions. Simulations are made for axial fill factor, pressure, temperature, and melting profiles. The results are validated experimentally. POLYM. ENG. SCI., 54:2362-2374, 2014

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0
9

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 35 publications
0
55
0
9
Order By: Relevance
“…Modelowanie globalne obejmuje kompletny opis procesu wytłaczania z uwzględnieniem: transportu tworzywa w stanie stałym, uplastyczniania tworzywa oraz przepływu uplastycznionego tworzywa (w cylindrze i głowicy wytłaczarki) [10,11,14,16]. Takie modelowanie wymaga całościowych obliczeń (w wielokrotnych pętlach iteracyjnych) w celu określenia punktu pracy wytłaczarki, definiowanego natężeniem przepływu tworzywa (wydajnością wytłaczania) i ciśnieniem wytłaczania.…”
Section: Modelowanie Globalne Procesu Wytłaczaniaunclassified
See 1 more Smart Citation
“…Modelowanie globalne obejmuje kompletny opis procesu wytłaczania z uwzględnieniem: transportu tworzywa w stanie stałym, uplastyczniania tworzywa oraz przepływu uplastycznionego tworzywa (w cylindrze i głowicy wytłaczarki) [10,11,14,16]. Takie modelowanie wymaga całościowych obliczeń (w wielokrotnych pętlach iteracyjnych) w celu określenia punktu pracy wytłaczarki, definiowanego natężeniem przepływu tworzywa (wydajnością wytłaczania) i ciśnieniem wytłaczania.…”
Section: Modelowanie Globalne Procesu Wytłaczaniaunclassified
“…przez modelowanie numeryczne MES (z wykorzystaniem metod elementów skończonych) [13,14]. Ostatnio zespół z udziałem autorów opracował pierwszy i na razie jedyny model wytłaczania jednoślimakowego z dozowanym zasilaniem wytłaczarki [15,16].…”
unclassified
“…[1][2][3] Flood fed single-screw extrusion is generally well understood, and the literature is very rich here. [16][17][18][19] Wilczyński et al [15,20,21] first developed a mathematical model of fusion of polymers in starve fed single-screw extruders, and subsequently a composite model of the process, first for conventional screws, and later for non-conventional screws. [7][8][9][10] Starve fed extrusion process is much less known.…”
Section: Introductionmentioning
confidence: 99%
“…7 The authors then developed the first composite model for starve-fed single screw extrusion processes, which involves metering, melting and solid conveying. 8,9 Derezinski 10 analysed the heat transfer in single screw extrusion to determine the melt temperature resulting from the combined effect of adiabatic heating generated by the screw and conduction heating by the barrel. He showed that the screw temperature can differ considerably from the melt temperature, particularly near the melting section inlet.…”
Section: Introductionmentioning
confidence: 99%